Woodland degradation effects on brea gum (Parkinsonia praecox) production - Von Müller, Axel Ricardo (2010)
A comparative study of the effects of woodland degradation on ‘‘brea’’ (Parkinsonia praecox) gum production was conducted in the Arid Chaco, Argentina, over a two-year period. We also analyzed the relationship of brea gum yield per tree with rainfall, tree size, soil water content, and other surrounding tree species. The results showed that the woodland degradation state has a strong effect on brea gum yield per tree, with the secondary woodland specimens being the most gum-productive during the dry seasons (p<0.0001). However, during wet years, we found that the woodland degradation state did not affect gum yield (p=0.5615). We found no significant differences in brea gum productivity per hectare between secondary woodland and degraded woodland colonized by Parkinsonia praecox (p>0.05). In both brea gum production per tree and hectare models, we found a significant covariation with the number of surrounding Prosopis spp. trees (p<0.0001), an indicator of good state woodland, which can improve soil water content and thereby enhance brea gum production. Moreover, the number of surrounding Prosopis spp. trees was the variable that best predicted brea gum yield in a replicated regression model (R2=0.41). The results of this study present the basis for a sustainable brea gum production in the Arid Chaco of Argentina.